Konstruksi Makna Penggunaan Avatar Oleh Mahasiswa Pengguna Aplikasi X Berdomisili Karawang (Studi Fenomenologi Tentang Motif dan Pengalaman Komunikasi) - Ahman Alpianto; Zainal Abidin; Tri Susanto (CV. ULIL ALBAB CORP, 2026)
The development of South Korean popular culture (Korean Wave) has influenced the way students express their identity on social media, one of which is through the use of Korean avatars in the X application. This phenomenon is not only visual, but also related to the meaning, motives, and communication experiences experienced by users. This study aims to understand the construction of meaning in the use of Korean avatars by X user students who live in Karawang, as well as to reveal the motives and communication experiences that underlie it. This study uses a qualitative method with an Alfred Schutz phenomenological approach. Data were obtained through in-depth interviews, observations, and documentation of three informants selected using a purposive sampling technique. The results show that the use of Korean avatars is interpreted in various ways by students, including as a representation of fandom identity, a strategy for managing self-image and privacy, and a source of inspiration and self-confidence. The motives for using avatars consist of a because motive influenced by past experiences and interest in Korean culture, and an in order to motive oriented towards the goal of building a digital persona and social acceptance. In the communication experience, Korean avatars play a role as a symbol that influences social interactions, increasing a sense of security and self-confidence, although not free from negative comments. This study confirms that the use of Korean avatars is a symbolic communication practice that reflects the process of negotiating students' identities in digital spaces.